Juegos de ficción, juegos electrónicos y metarrepresentación infantil (2007)
ABSTRAC: The metarrepresentation is a cognitive mechanism whose main function focuses on the capacity that have the "normal subjects" think or imagine the mental state of another individual and develops during childhood under certain conditions of social interaction. The article presents some reflections on the relationship between the formation of metarrepresentation in children and use of fictional games and electronic.